2022
DOI: 10.7717/peerj.13565
|View full text |Cite
|
Sign up to set email alerts
|

Population structure in Quercus suber L. revealed by nuclear microsatellite markers

Abstract: Quercus suber L. is a sclerophyllous tree species native to the western Mediterranean, a region that is considered highly vulnerable to increased temperatures and severe dry conditions due to environmental changes. Understanding the population structure and demographics of Q. suber is essential in order to anticipate whether populations at greater risk and the species as a whole have the genetic background and reproductive dynamics to enable rapid adaptation. The genetic diversity of Q. suber has been subject … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…We could not detect any notable population structure among the F. sylvatica stands in the surveyed area. While the estimated mean FST of 0.039 was already quite low compared to other forest trees [30][31][32] , this value is likely an overestimate as the comparison with the differentiation among growth classes within stands showed (Fig. 4).…”
Section: Discussionmentioning
confidence: 81%
“…We could not detect any notable population structure among the F. sylvatica stands in the surveyed area. While the estimated mean FST of 0.039 was already quite low compared to other forest trees [30][31][32] , this value is likely an overestimate as the comparison with the differentiation among growth classes within stands showed (Fig. 4).…”
Section: Discussionmentioning
confidence: 81%
“…The samples were collected from individuals of natural stands and provenance trials. Structure analyses results showed that Q. suber contains three major genetic clusters that correspond to a rough division of east-west areas, with Corsica belonging to a third cluster [45]. This cluster arrangement suggests that differentiation occurred by isolation in refugia, and then, when populations expanded, there may have been contact between isolated species and introgression from other Quercus species [45].…”
Section: Hybrid Parental Species Reference Observationsmentioning
confidence: 94%
“…Quercus × pacensis Quercus faginea Lam. × Q. suber [44] Rare in Southern Portugal, pure Q. faginea can develop a corky bark thanks to secondary growth More recently, Sousa et al [45] studied the population structure patterns of Q. suber by using 13 nuclear microsatellite markers in individuals from 17 distinct locations across the entire range of the species. The samples were collected from individuals of natural stands and provenance trials.…”
Section: Hybrid Parental Species Reference Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintained genetic diversity in crop plants could also help the crops populations to evolve and cope up themselves with the current environmental changes by maintaining the sustainability of crops species in agricultural production system. Genetic diversity serves as the foundation for adaptation and speciation, serving as the "brick" of evolution [71], if there is little or no genetic diversity with cultivated crops, the probability of the crops to cope up with the changing environment and susceptibility to wide spread disease will aggravate. In line with these, efforts have been made by many scientists to investigate crop genetic diversity using different markers system and generated considerable amount of information about genetic diversity that existed in conserved or actively utilized genotypes [72].…”
Section: Patterns Of Genetic Diversity Within and Among Populationsmentioning
confidence: 99%